A Novel in-Band OSNR Measurement Method Based on Normalized Autocorrelation Function - Zhuili Huang; Jifang Qiu; Deming Kong; Ye Tian; Yan Li; Hongxiang Guo; Xiaobin Hong; Jian Wu (IEEE Photonics Journal, 2018)
We propose and experimentally demonstrate a novel in-band optical signal-to-noise ratio (OSNR) measurement method based on normalized autocorrelation function. Experimental results indicate that OSNR of four-channel 32-Gbaud pulse-duration modulation-QPSK wavelength-division-multiplexing signals is precisely measured with applicability to flexible channel spacing. The measurement range is 37 dB from −15 to 22 dB with error less than $ ± 0.5$ dB. The proposed method is also robust to bit rate, modulation format, chromatic dispersion, and input optical power. Besides, the choice of delay in calculation of normalized autocorrelation function is flexible from 1.6 to 30 ps.